Polypropylene composition as well as preparation method and application thereof
By introducing concave and convex rod soil and high alumina glass fibers into the polypropylene resin, and using initiators and crosslinking agents to form a mesh structure, the problem that polypropylene materials are prone to peristalsis under high temperature and high pressure is solved, and the product's high creep resistance and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411758925.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Polypropylene materials are prone to peristalsis under long-term stress or high temperature environments, resulting in plastic deformation, and existing modified materials may lead to product rigidity imbalance and appearance problems.
The polypropylene resin matrix is introduced into the polypropylene resin matrix, and the composite filler with a mesh structure is formed by combining the initiator and crosslinking agent to improve the product's creep resistance and mechanical properties.
It effectively improves the product's resistance to external force and temperature, ensures the product's sufficient rigidity and toughness, and avoids appearance problems. It is suitable for automotive cooling system components.
Smart Images

Figure BDA0005167078970000071 
Figure BDA0005167078970000081 
Figure BDA0005167078970000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a polypropylene composition and a preparation method and application thereof. Background Art
[0002] Polypropylene material has excellent physical properties, chemical stability and processing performance, but under long-term stress or high temperature environment, it is extremely prone to creep, which in turn causes plastic deformation problems.
[0003] In automobile cooling systems, it is often necessary to involve long-term dynamic changes in temperature and pressure, so it is generally difficult to use polypropylene-based composite materials with poor creep resistance. For this reason, people try to improve the creep phenomenon of products by adding modified materials, such as adding large doses of inorganic fillers to reduce the dynamic fluidity of products, or adding nano-nucleating agents to improve the crystallinity of polypropylene resins. However, such practices may lead to an imbalance in the rigidity and toughness of the product, making it difficult to use in automotive parts, and may even cause obvious appearance problems. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a polypropylene composition, which introduces attapulgite and high-aluminum glass fiber composite filler into the matrix resin, and then compounded with an initiator and a cross-linking agent, so that the product is based on the network structure of the filler as the support and the strong force of the polypropylene molecular weight, which can not only effectively improve the product's resistance to external force and temperature, but also ensure that the product has sufficient rigidity and toughness, and will not have appearance problems.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A polypropylene composition comprising the following components in parts by weight:
[0007] 59-71 parts of polypropylene resin, 20-40 parts of high-aluminum glass fiber, 2-8 parts of attapulgite, 1-3 parts of compatibilizer, 0.01-0.2 parts of peroxide initiator, 0.5-1.5 parts of vinyl silane crosslinking agent;
[0008] The alumina content of the high-aluminum glass fiber is ≥30wt%.
[0009] Preferably, the peroxide initiator includes at least one of dibenzoyl peroxide, dodecyl peroxide and dicumyl peroxide.
[0010] In the technical solution of the present invention, in order to improve the creep resistance of the product while ensuring that the mechanical strength of the product can be maintained at a relatively good level, the inventor introduced attapulgite and high-aluminum glass fiber into the polypropylene resin matrix. Attapulgite has high dispersibility and a special needle-rod structure. When compounded with glass fiber, it will form a composite structure similar to a fiber mesh. This structure has high mechanical ability and can provide a supporting skeleton in multiple force directions with high force balance. High-aluminum glass fiber has ideal mechanical strength and can improve the creep resistance of the product without introducing a large dose. At the same time, this glass fiber will not easily break or fracture after processing or when subjected to force, which can ensure the rigidity of the product. On the other hand, the peroxide initiator will decompose into free radicals under heating. Taking dibenzoyl peroxide as an example, in polypropylene When in the resin matrix, it will decompose to generate benzoyl radicals and phenyl radicals after heating. This highly active free radical will attack the hydrogen atoms on the polypropylene molecular chain to form polypropylene macromolecular chain free radicals. At this time, this polypropylene macromolecular chain free radical will act on the vinyl double bond of the vinyl silane cross-linking agent to form a free radical intermediate, and the cross-linking agent in the free body will further undergo hydrolysis or condensation reaction to produce silanol groups. In the condensation reaction, Si-O-Si bonds are formed through the dehydration reaction between Si-OH groups. These Si-O-Si bonds rivet the polypropylene molecular chains together, so that the originally loose polypropylene molecular chains form a dense cross-linking network, which not only improves the melt strength, deformation resistance and anti-slip properties of the polypropylene resin matrix, but also can effectively bond to the filler skeleton, ultimately achieving ideal creep resistance.
[0011] If other fillers and glass fibers are used, the supporting strength of the filler skeleton cannot be guaranteed. If ordinary glass fibers are used to construct the skeleton, not only the mechanical strength of the product may not be guaranteed, but its creep resistance will also be at a low level. Even inappropriate filler compounding may cause appearance problems. On the other hand, initiators and crosslinkers are the key to whether the polypropylene resin can form a dense body. If the types are changed or missing, the creep resistance of the product will be seriously weakened.
[0012] Preferably, the polypropylene composition comprises the following components in parts by weight:
[0013] 60-70 parts of polypropylene resin, 23-38 parts of high-aluminum glass fiber, 4-6 parts of attapulgite, 1-3 parts of compatibilizer, 0.01-0.2 parts of peroxide initiator, and 0.5-1.5 parts of vinyl silane crosslinking agent.
[0014] More preferably, the mass content of the polypropylene resin in the polypropylene composition is ≥50wt%.
[0015] Preferably, the alumina content of the high-aluminum glass fiber is 30-32wt%.
[0016] More preferably, the high-aluminum glass fiber has an average length of 2 to 5 mm and an average diameter of 7 to 10 μm.
[0017] More preferably, the alumina content, average length and average diameter of the high-aluminum glass fiber are tested as follows: the glass fiber is uniformly dispersed in water, the length of the glass fiber is tested using a two-dimensional element, the glass fiber is observed using a scanning electron microscope and the diameter of the glass fiber is confirmed using mapping software, the number of tested glass fibers is not less than 50, and the test results are averaged; the alumina content of the glass fiber is determined with reference to GB / T 1549-2008.
[0018] More preferably, the vinyl silane crosslinking agent is a vinyl silane coupling agent;
[0019] More preferably, the vinyl silane coupling agent includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane.
[0020] Preferably, the average length of the attapulgite is 0.5 to 5 μm.
[0021] More preferably, the average length of the attapulgite is in the range of one or any two of 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm.
[0022] Preferably, the average diameter of the attapulgite is 10 to 30 nm.
[0023] More preferably, the test method for the average particle size of the attapulgite is: uniformly disperse the attapulgite in water, use two-dimensional measurement to test the length of the attapulgite, observe the attapulgite with a scanning electron microscope and use mapping software to confirm the diameter of the attapulgite, test no less than 50 attapulgites, and take the average value of the test results.
[0024] Preferably, the ratio of the average length (μm) of the high-aluminum glass fiber to the average length (μm) of the attapulgite is (1500-5000):1;
[0025] More preferably, the ratio of the average length (μm) of the high-aluminum glass fiber to the average length (μm) of attapulgite is (2000-3500):1.
[0026] As mentioned above, high-aluminum glass fiber and attapulgite will form a stacked network structure after compounding, and under the action of initiator and cross-linker, polypropylene resin will further cross-link on the network structure to form a dense and multi-directionally resistant composite. When the glass fiber as the main skeleton and the attapulgite as the filling component are of different sizes, the looseness of the network they form will also change, which in turn affects the mechanical properties and creep resistance of the product. Under the above preferred ratio, the riveting effect of high-aluminum glass fiber and attapulgite is the best, the network structure is the most uniform, especially when the initiator and cross-linker interact with polypropylene, it will not cause the attapulgite agglomeration problem, and the comprehensive performance of the product is the best.
[0027] More preferably, the average length of the attapulgite is 1 to 2 μm.
[0028] More preferably, the initiator is dicumyl peroxide, and the crosslinking agent is vinyltrimethoxysilane.
[0029] When this cross-linking auxiliary agent system is selected, the creep resistance of the prepared composite polypropylene composition is optimal.
[0030] Preferably, the polypropylene resin has a melt flow rate of 10 to 80 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.
[0031] Preferably, the polypropylene composition further comprises a compatibilizer.
[0032] More preferably, the weight proportion of the compatibilizer is 1 to 3 parts.
[0033] More preferably, the compatibilizer is maleic anhydride grafted polypropylene, and the grafting rate is 0.8-1.5%.
[0034] The grafting rate of maleic anhydride can be determined by infrared spectroscopy: a sample of fixed thickness is tested by Fourier transform infrared spectrometer to obtain characteristic absorption peaks of infrared spectrum, and the grafting rate of maleic anhydride can be calculated by comparing the ratio of the carbonyl and methylene absorption intensities.
[0035] Preferably, the polypropylene composition further comprises a lubricant.
[0036] More preferably, the weight portion of the lubricant is 0.1 to 0.5 parts.
[0037] More preferably, the lubricant is stearate.
[0038] Preferably, the polypropylene composition further comprises an antioxidant.
[0039] More preferably, the weight portion of the antioxidant is 0.1 to 0.5 parts.
[0040] More preferably, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.
[0041] More preferably, the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant, and the mass ratio of the two is (0.8-1.2): (1.8-2.2).
[0042] It should be noted that, based on the needs of actual products, technicians in this field can appropriately introduce some components commonly introduced into polypropylene products without affecting the performance of the product, such as antioxidants to improve the conventional oxidation resistance of the product, lubricants to improve the processing performance of the product, etc., and there is no need to specifically limit the types of components.
[0043] Another object of the present invention is to provide a method for preparing the polypropylene composition, comprising the following steps:
[0044] The components are added into a screw extruder for melt extrusion and granulation to obtain the polypropylene composition.
[0045] Preferably, the heating temperature of the screw extruder is 180-220° C., and the screw speed is 400-600 rpm.
[0046] The preparation method of the polypropylene composition of the present invention is simple, has low requirements on equipment, and can realize industrial-scale production.
[0047] Another object of the present invention is to provide use of the polypropylene composition in preparing automotive cooling system parts.
[0048] In the automobile cooling system, in addition to metal connecting parts and internal protective parts, many parts are made of plastic. Due to the working mechanism of the system, the metal connecting parts will often transfer heat to the plastic parts, making them stay at a high temperature for a long time. In addition, the metal parts have thermal expansion and contraction effects, so some plastic parts are often subjected to external pressure, and then obvious creep deformation occurs. The polypropylene composition described in the technical solution of the present invention introduces specific functional additives and composite fillers while ensuring the basic mechanical properties, so that the creep resistance of the overall product is greatly improved, and it can maintain relative stability under high temperature and high pressure, and there will be no obvious appearance problems. Therefore, it is very suitable for application in automobile cooling system parts.
[0049] Preferably, the automobile cooling system components include an inner liner heat sink, a heat insulation sleeve, an exhaust fan, and metal buckles.
[0050] The beneficial effect of the present invention is that the present invention provides a polypropylene composition, which introduces attapulgite and high-aluminum glass fiber composite filler into the matrix resin, and then compounded with an initiator and a cross-linking agent, so that the product is based on the network structure filler as support and the strong force of the polypropylene molecular weight, which can not only effectively improve the product's resistance to external force and temperature, but also ensure that the product has sufficient rigidity and toughness, and will not have appearance problems. DETAILED DESCRIPTION
[0051] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0052] Examples 1 to 11
[0053] An embodiment of a polypropylene composition and a preparation method and application thereof according to the present invention, the components of the polypropylene composition are shown in Table 1.
[0054] The method for preparing the polypropylene composition comprises the following steps:
[0055] The components are mixed uniformly and then melt-extruded and granulated in a screw extruder to obtain the polypropylene composition.
[0056] When the components are melt-extruded, the temperature zones of the twin-screw extruder are set to 180°C in zone 1, 180°C in zone 2, 180°C in zone 3, 180°C in zone 4, 180°C in zone 5, 180°C in zone 6, 180°C in zone 7, 180°C in zone 8, 180°C in zone 9, and 200°C in zone 10, the screw speed is 500rpm, and the screw aspect ratio is 40:1.
[0057] Comparative Examples 1 to 8
[0058] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0059] Among the components described in each embodiment and comparative example,
[0060] The polypropylene resin 1 is PP Z30S produced by Sino-Korea Petrochemical, and according to ISO 1133-2011, the melt flow rate at 230°C and 2.16kg load is 25g / 10min;
[0061] The polypropylene resin 2 is PP M1200HS produced by Shanghai Petrochemical, and according to ISO 1133-2011, the melt flow rate at 230°C and 2.16kg load is 12g / 10min;
[0062] The high-aluminum glass fiber 1 is Advantex 149H produced by Owens Corning, with an alumina content of 30wt%, an average length of 4mm, and an average diameter of 8μm;
[0063] The high-aluminum glass fiber 2 is Advantex 248 produced by Owens Corning, with an alumina content of 32wt%, an average length of 3mm, and an average diameter of 9μm;
[0064] The glass fiber is ECS301HP-3-H produced by Chongqing Fiberglass, with an alumina content of 25wt%, an average length of 3mm, and an average diameter of 9μm;
[0065] The talcum powder is TYT-777A produced by Liaoning Haicheng Tianyuan Chemical Co., Ltd., and the average particle size after screening is 8 μm;
[0066] The attapulgite 1 to 5 are obtained by using TS003 produced by Zhongcai Attapulgite as raw material and screening and grading;
[0067] The attapulgite 1 has an average length of 1.2 μm and an average diameter of 18 nm after screening;
[0068] The attapulgite 2 has an average length of 1.6 μm and an average diameter of 20 nm after screening;
[0069] The attapulgite 3 has an average length of 1.9 μm and an average diameter of 20 nm after screening;
[0070] The attapulgite 4 has an average length of 0.8 μm and an average diameter of 22 nm after screening;
[0071] The attapulgite 5 has an average length of 2.6 μm and an average diameter of 19 nm after screening;
[0072] The diatomite powder is 499 product produced by Yirui Stone, with an average particle size of 1.5 μm;
[0073] The compatibilizer is CA100 produced by Arkema, France, maleic anhydride grafted polypropylene, with a grafting rate of 1.1%;
[0074] The initiator 1 is dibenzoyl peroxide produced by Jinan Guochen Taifu;
[0075] The initiator 2 is dicumyl peroxide produced by Guangzhou Fangruida Chemical;
[0076] The initiator 3 is zinc diethyldithiocarbamate ZDEC produced by Shanghai Puzhen Technology;
[0077] The crosslinking agent 1 is V823925 produced by Maclean, vinyl trimethoxy silane;
[0078] The crosslinking agent 2 is KH-151 produced by Jessica, vinyl triethoxysilane;
[0079] The crosslinking agent 3 is TMPTA, trimethylolpropane triacrylate, produced by Kanos Technology;
[0080] The lubricant is commercially available zinc stearate;
[0081] The antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant produced by BASF: antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2.
[0082] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0083] Table 1
[0084]
[0085] Table 2
[0086] Component weight Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Polypropylene resin 1 65 65 65 65 65 65 65 65 High Aluminum Fiberglass 1 35 30 30 30 30 30 Fiberglass 30 talcum powder 30 Compatibilizer 2 2 2 2 2 2 2 2 Attapulgite 1 5 5 5 5 5 5 diatomite 5 Initiator 1 0.1 0.1 0.1 0.1 0.1 0.1 Initiator 3 0.1 Crosslinker 1 1 1 1 1 1 1 Crosslinker 3 1 Lubricants 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 Antioxidants 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3
[0087] In order to verify the performance of the polypropylene composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0088] (1) Bending strength test: Each product was injection molded into a 150*10*4 mm test square plate and tested according to the ISO 527-2-2012 test standard at a test speed of 50 mm / min;
[0089] (2) Izod notch impact strength test: Each product was injection molded into a test square plate of 80*10*4 mm and tested according to the ISO180 / 1eA-2010 test standard, A-type notch;
[0090] (3) Creep resistance test: The test is conducted in accordance with GB / T 11546.2-2022. Each product is injection molded into a test square plate of 80*10*4 mm with a span of 64 mm. The bending load is set at 75% of the bending strength of the sample. The test temperature is 120°C and the adjustment time is 24 h. The creep resistance of the sample is evaluated by measuring the time it takes for the sample to reach a predetermined bending strain value (1.5 times the thickness of the sample) under a constant load. Under the same conditions, the longer the time, the better the creep resistance of the product.
[0091] (4) Appearance performance test: Each product is injection molded into a test square plate of 80*10*4mm, and the surface is observed for defects such as floating fibers, particles, and depressions.
[0092] The test results are shown in Tables 3 and 4.
[0093] Table 3
[0094]
[0095] Table 4
[0096]
[0097] It can be seen from Tables 3 and 4 that the polypropylene composition of the present invention can achieve a relatively high level of rigidity and toughness (the flexural strength can reach more than 245 MPa, and the Izod notched impact strength can reach 18 KJ / m 2 The creep resistance is significantly improved, and the creep time can reach more than 25h. The main reason lies in the design of the composite mesh skeleton of inorganic filler and the densification design of polypropylene resin under the action of initiator and crosslinking agent. At the same time, under the design, the product has no obvious appearance problems and the overall performance is excellent. According to Example 1 and Examples 5 to 8, it can be seen that when designing the composite inorganic filler mesh skeleton, the size of high-aluminum glass fiber and attapulgite has a certain influence on its skeleton structure, density and uniformity. When the ratio of the average length (μm) of high-aluminum glass fiber to the average length (μm) of attapulgite is within the range of (2000 to 3500): 1, the creep resistance time of the product is longer, the bending strength and notched impact strength are also better, and the comprehensive performance is better. On the other hand, for the densification design of polypropylene resin, as can be seen from Examples 1 and Examples 9 to 11, when diisopropylbenzene peroxide and vinyltrimethoxysilane are preferably matched, the comprehensive performance of the product is better.
[0098] In contrast, the product described in Comparative Example 1 only introduces high-aluminum glass fiber when constructing the inorganic filler skeleton, which cannot effectively cross-link with the polypropylene resin and has insufficient multi-directional resistance. Therefore, the mechanical properties and creep resistance of the product are not good. In Comparative Example 2, the attapulgite is replaced with conventional small-sized filler diatomaceous earth. Obviously, it does not form an ideal skeleton structure with the high-aluminum glass fiber, and the creep resistance of the product is poor. In Comparative Example 3, the high-aluminum glass fiber is replaced with ordinary glass fiber. Due to its poor mechanical strength, when used as the main body of the skeleton, it not only cannot provide sufficient basic mechanical properties for the product, but also has insufficient riveting strength for the resin. The product has a high degree of deformation and creep. The product of Comparative Example 4 uses a talcum powder system and attapulgite, which is also a very common polypropylene filler system at present. However, this system cannot effectively achieve high dispersibility and high mechanical strength after the polypropylene resin is initiated and cross-linked, and even has appearance problems. Therefore, it is obviously impossible to use it in automobile cooling systems. It can be seen from Comparative Examples 5 to 8 that, in addition to the network skeleton, if the polypropylene resin is not properly initiated and cross-linked, the product still cannot achieve high creep resistance, and the organic system and inorganic system of the product actually have obvious synergistic effect.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene composition, characterized in that The composition comprises the following components in parts by weight: 59-71 parts of polypropylene resin, 20-40 parts of high-aluminum glass fiber, 2-8 parts of attapulgite, 1-3 parts of compatibilizer, 0.01-0.2 parts of peroxide initiator, 0.5-1.5 parts of vinyl silane crosslinking agent; The alumina content of the high-aluminum glass fiber is ≥30wt%.
2. The polypropylene composition according to claim 1, characterized in that The peroxide initiator includes at least one of dibenzoyl peroxide, dodecyl peroxide, and dicumyl peroxide; the vinyl silane crosslinking agent is a vinyl silane coupling agent; the vinyl silane coupling agent includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, and vinyl tri(β-methoxyethoxy) silane.
3. The polypropylene composition according to claim 1, characterized in that The alumina content of the high-aluminum glass fiber is 30-32wt%; the average length of the high-aluminum glass fiber is 2-5mm, and the average diameter is 7-10μm.
4. The polypropylene composition according to claim 1, characterized in that The average length of the attapulgite is 0.5 to 5 μm; the average diameter of the attapulgite is 10 to 30 nm.
5. The polypropylene composition according to claim 3 or 4, characterized in that The ratio of the average length of the high-aluminum glass fiber to the average length of the attapulgite is (1500-5000):
1.
6. The polypropylene composition according to claim 1, characterized in that The polypropylene resin has a melt flow rate of 10 to 80 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.
7. The polypropylene composition according to claim 1, characterized in that The components of the polypropylene composition also include a compatibilizer; the components of the polypropylene composition also include a lubricant; and the components of the polypropylene composition also include an antioxidant.
8. The method for preparing the polypropylene composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The components are added into a screw extruder for melt extrusion and granulation to obtain the polypropylene composition.
9. The method for preparing the polypropylene composition according to claim 8, characterized in that: The heating temperature of the screw extruder is 80-220° C., and the screw speed is 400-600 rpm.
10. Use of the polypropylene composition according to any one of claims 1 to 7 in the preparation of automotive cooling system parts.
11. The use according to claim 10, characterized in that The automobile cooling system components include an inner liner heat sink, a heat insulation sleeve, an exhaust fan, and metal buckles.
12. A component of an automobile cooling system, characterized in that: The polypropylene composition comprises the polypropylene composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Application and preparation method of glass fiber with low crystallization temperature, low crystallization speed, high temperature resistant property, and ultrahigh aluminum content and composite material
CN105645774A
Shockproof polystyrene foam material
CN111117092A
Reinforced polypropylene material and preparation method thereof
CN111154183A
High-strength flame-retardant polypropylene composite material and preparation method thereof
CN117866336A
Functionalized propylene polymer compositions and composites containing same
US20060025526A1